Reuse and variability in large software applications. - Estublier, Jacky
Reuse has always been a major goal in software engineering, since it promises large gains in productivity, quality and time to market reduction. Practical experience has shown that substantial reuse has only successfully happened in two cases: libraries, where many generic and small components can be found; and product lines, where domains-specific components can be assembled in different ways to produce variations of a given product.In this paper we examine how product lines have successfully achieved reuse of coarse-grained components, and the underlying factors limiting this approach to narrowly scoped domains. We then build on this insight to present an approach, called software federation, which proposes a mechanism to overcome the identified limitations, and therefore makes reuse of coarse-grained components possible over a larger range of applications. Our approach extends and generalizes the product line approach, extending the concepts and mechanisms available to manage variability. The system is in use in different companies, validating the claims made in this paper.
Keywords: Software; Software engineering; Design tools and techniques; Software architectures; Interoperability; Programming environments; Design; Experimentation; AOP; COTS; EAI; MDA; Interoperability; Model driven software engineering; Process driven application; Product families; Product line; Reuse; Variability; Workflow